(untitled) (THE ACADEMIA, 2026)
Nepal has traditionally been positioned as a crucial area of strategic rivalry in South Asia due to its placement between China and India. India has historically asserted defense and security dominance in Nepal through treaties, joint exercises, and sharing of intelligence, for the purpose of ensuring its northern frontier. While India has been worried about Nepal’s increasing proximity with China, China’s growing presence in Nepal—via infrastructure development under the Belt and Road Initiative, deepening political engagement, and extensions into the Terai and Himalayan border regions—has unsettled New Delhi. India perceives these activities as security challenges to its Indo-Gangetic core, particularly in terms of the historical and unresolvable border disputes such as the Kalapani-Limpiyadhura-Lipulekh tri-junction issue. The objective of the study is to examine how Nepal’s defense relations with India have been evolving, analyze the character of China’s strategic influence in Nepal, and examine the role of border politics in generating triangular dynamics in the India–Nepal–China relationship. Methodologically, the study relies on a qualitative approach, drawing upon secondary sources including treaties, government documents, policy declarations, and academic literature. This allows for situating historical trends and mapping shifts in bilateral and trilateral security relations. The analysis is grounded in a geopolitical and security studies approach, observing how Nepal’s policy space and India’s strategic action are molded by material interests, strategic geography, and asymmetrical power relations. The paper contends that although India must protect its most important interests, an over-reliance on coercive tactics, such as economic embargoes or intrusive military pressures, may drive Nepal away and bolster China. The most lasting regional balance approach is a balanced policy that incorporates both defense cooperation and diplomatic sensitivities.